New MS Drugs - Rizzo, Toni (MD Conference Express, 2012)
Multiple sclerosis (MS) affects more than 350,000 people in the United States (US) and 2.5 million people worldwide. In the US alone, the health care costs that are associated with the treatment of MS are estimated to be more than 10 billion annually. Recently approved or investigational agents in advanced development have the potential to significantly improve outcomes for patients with relapsing-remitting MS [Fox EJ, Rhoades RW. Curr Opin Neurol 2012].